2021
DOI: 10.3390/healthcare9091237
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Factors Associated with Nonadherence to Medications in Patients with Chronic Diseases?

Abstract: Introduction: Adherence to medications is very crucial for an optimized clinical outcome in the management of chronic diseases. Beliefs about medications and other factors can significantly affect adherence to chronic medications. The objective of the present research was to identify the associated factors of adherence to medication in Jordanian patients with chronic diseases utilizing a stepwise binary logistical regression model. Methods: A cross-sectional study was carried out between November 2018 and Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
11
3
Order By: Relevance
“…The concept of “concordance” describes how patient agreement to receive a particular medication is expected to improve the experience with this medication, hence improving the acceptance of the medication [ 38 ]. Exploration of patients’ beliefs can explain medication use and identify barriers that can be resolved to improve medication usage [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of “concordance” describes how patient agreement to receive a particular medication is expected to improve the experience with this medication, hence improving the acceptance of the medication [ 38 ]. Exploration of patients’ beliefs can explain medication use and identify barriers that can be resolved to improve medication usage [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, adherence rate was calculated to be 32%. Furthermore, factors identified to be influencing adherence to medications were necessity and concerns beliefs, dosage frequency and having medical [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-communicable chronic diseases accounted for 78% of deaths in 2018 [ 6 ]. Several published studies have reported low adherence in Jordanian patients with several chronic diseases including diabetes mellitus and dyslipidemia [ 7 9 ], which influenced health outcomes [ 10 ]. Similar to the other parts of the globe, the issue of non- adherence to medications in Jordanian chronically ill patients is challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SGLT2 inhibitors can decrease glucose reabsorption and depress the renal threshold, elevating glucose in urine discharge [4]. Furthermore, it can be utilized to manage diabetes mellitus Type 2 (T2DM), besides food, and enhance glycemic control in individuals with type 2 diabetes [5]. Further, the use decreases cardiovascular disease hazard in a patient with T2DM and cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%